Analisis Tindak Tutur Ekspresif dan Direktif pada Video Edukasi Bertema Sains dalam Kanal YouTube Kok Bisa? - Juni Us’ariasih; Talitha Febiola; Anisah Ryan Putri Herlina; Rifqi Nandana Mahardika; Najmi Ali Mumtaz; Asep Purwo Yudi Utomo; Arka Yanitama (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Language is a communication tool used to express an idea or emotion. In linguistics, language is comprehensively explored with the aim of developing understanding and is also used for research. In analyzing the meaning of language, a pragmatic understanding is required. Pragmatics is a linguistic field that examines the interplay between the function and form of speech acts. This research primarily focuses on the analysis of expressive and directive speech acts. Expressive speech acts involve utterances that convey the feelings or thoughts experienced by the speaker. On the other hand, directive speech acts involve utterances intended to encourage or trigger action from the listener. This research aims to obtain, examine, and discuss a variety of speech acts found in educational science-themed videos on the YouTube channel "Kok Bisa?". This research is a qualitative descriptive study using a theoretical approach, namely a pragmatic approach. The data used consists of a number of utterances in the videos. The data collection technique used is observation and note-taking. Data analysis is carried out using distributional and correlational techniques. Data presentation is done formally and informally. The potential value of this study lies in its capacity to offer insights to the author and researchers concerning expressive and directive speech acts found in utterances. The practical benefits of this research will be obtained by those in the field of science, educators, learners, and language researchers as a basis, reference, and teaching material concerning expressive and directive speech acts found within utterances. In the science videos on the "Kok Bisa?" YouTube channel, 26 expressive speech acts and 36 directive speech acts were identified from nine selected videos. This analysis reveals that directive speech acts in the form of questioning dominate these videos, enabling two-way interaction through viewer comments.